التحري عن إيجابية Anti-HBc عند مرضى التحال الدموي المصابين بالتهاب الكبد C - يازجي, هيثم; البودي, مي جميل (Latakia University Journal -Medical Sciences Series, 2013)
تهدف هذه الدراسة إلى تحديد معدل انتشار أضداد المستضد اللبيAnti-HBc لفيروس التهاب الكبد B (HBV) عند مرضى التحال الدموي، وتقييم دورها بوصفه مؤشراً في تشخيص التهاب الكبدB الخفي عند المرضى المصابين بالتهاب الكبد C. شملت عينة الدراسة 122 مريضاً تحال دموي من أربع مستشفيات في سورية بمتوسط عمري 54.03 عاماً ، وتلقوا لقاح التهاب الكبد B وهم سلبيو المستضد السطحي (العامل الأسترالي) HBsAg. واستخدمت طريقة الإليزا (ELISA) لدراسة انتشار الأضداد اللبية عند مرضى الدراسة، واستخدمت طريقة تفاعل البوليميراز التسلسلي بالزمن الحقيقيPolymerase Chain Reaction - real time (PCR-RT) عند المرضى إيجابيي الأضداد اللبية. أظهرت النتائج أن نسبة إيجابيي الأضداد اللبية Anti-HBc كانت (29%) من مجموعة الشاهد و(47%) من المرضى المصابين بالتهاب الكبد C. وفي المرحلة التالية تم التحري عن HBV DNA باستخدام PCR –RT وذلك لـ34 مريضاً إيجابيي الأضداد اللبية ومصابين بالتهاب الكبد C وتبين بأن (12%) مصابون بالتهاب الكبد B الخفي وهي تعد نسبة مرتفعة بالمقارنة مع نسبة انتشار التهاب الكبد Bفي سورية والمقدرة بـ 5 %. تظهر نتائج هذه الدراسة أهمية إجراء اختبار التحري عن الأضداد اللبية Anti-HBc فضلاً عن المستضد This study aims to determine the prevalence of antibodies to hepatitis B core antigen )anti-HBc) in hemodialysis patients, and evaluate its role as an indicator for the diagnosis of Occult hepatitis B (OHB) in patients with hepatitis C. A study sample included 122 patients from four hospitals in Syria. All patients had undergone 3-4 hour hemodialysis sessions twice weekly, and received a hepatitis B vaccine, and they are negative for hepatitis B surface antigen (HBsAg). Patients ranged in age between 21 -79 years (median age 54.03 years old), and the method used to study the prevalence of anti-HBc in hemodialysis patients is enzyme-linked immunosorbent assay (ELISA) and Polymerase Chain Reaction-real time (RT-PCR. The results showed that 14 patients (29%) of the control group, and 34 patients (47%) of hepatitis C positive patients are Anti-HBc positive. In the next step, HBV DNA was detected using RT-PCR technique for 34 positive anti-HBc, hepatitis C infected patients. Results showed that 4 patients (12%) have Occult hepatitis B; this rate is considered high compared with the prevalence of hepatitis B in Syria, which is estimated at 5%. The results of this study confirm the importance of a screening test for anti-HBc in addition to screening for HBsAg, as positivity of anti-HBc may be a possible indicator of Occult hepatitis B infection in patients with hepatitis C subjected to hemodialysis devices.